Local and Neighboring Effects of China’s New Energy Demonstration City Policy on Inclusive Green Growth - Yalin Duan; Hsing Hung Chen; Yuting Deng (Energies)
Amid mounting global climate change, resource scarcity, and environmental pressures, regional economies are accelerating their transition towards green and inclusive growth models. This research examines how China’s New Energy Demonstration City (NEDC) policy influences inclusive green growth (IGG), including its underlying mechanisms. Harnessing policy interventions as quasi-natural experiments, we use 2006–2022 panel datasets of 284 Chinese cities to develop a spatial difference-in-differences (SDID) model for causal inference. The findings are as follows: (1) The NEDC policy significantly enhances IGG in pilot cities while generating positive spatial spillover effects on neighboring cities, exhibiting an inverted U-shaped pattern; (2) The policy effects demonstrate pronounced regional heterogeneity, with the strongest impact observed in western China; (3) Mechanism analysis confirms that green technology innovation serves as a critical pathway through which the NEDC policy drives IGG. These findings provide robust empirical evidence for designing scalable policy promotion mechanisms and refining innovation-driven governance frameworks.